"High ankle block" for surgery at the ankle joint. Issue 8 (December 2022) - Hofmann-Kiefer, Klaus F.; Gaube, Federico; Groene, Philipp; Böcker, Wolfgang; Polzer, Hans; Baumbach, Sebastian F.
Abstract: Background: Surgery around the ankle is increasingly embedded in outpatient treatment concepts. Unfortunately, the classic "ankle block" as a concept of regional anesthesia is inappropriate for surgery around the ankle because the injection sites are too distal to block this specific region. Methods: The "high ankle block" avoids this disadvantage by dislocating the injection points 15 cm proximal to the malleoli. Three of five peripheral nerves necessary to perform the block can be reached by a circumferential subcutaneous wall. The Posterior Tibial Nerve and the Deep Peroneal Nerve are addressed by an ultrasound guided approach. Results: The efficacy of the technique is highlighted by a case series (3 cases) in which the new blockade was used as a stand-alone procedure, i.e. without additional general anesthesia. Conclusions: The "high ankle block" may serve as an ultrasound guided expansion to the classic techniques, extending the operative spectrum to the ankle region.